1988
DOI: 10.1007/bf00441979
|View full text |Cite
|
Sign up to set email alerts
|

Infantile cortical hyperostosis associated with the Wiskott-Aldrich syndrome

Abstract: A case report of an infant with the Wiskott-Aldrich syndrome and clinical and radiological features of infantile cortical hyperostosis (Caffey disease) is presented. This is the third case described of the association of these two rare disorders and gives further support to the role of an immunologic defect in the pathogenesis of infantile cortical hyperostosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…He rapidly deteriorated and eventually succumbed to a generalised CMV infection associated with intracranial haemorrhage. Interestingly, X-rays revealed classical changes of infantile cortical hyperostosis which is now a well described finding with WAS (14,15).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…He rapidly deteriorated and eventually succumbed to a generalised CMV infection associated with intracranial haemorrhage. Interestingly, X-rays revealed classical changes of infantile cortical hyperostosis which is now a well described finding with WAS (14,15).…”
Section: Resultsmentioning
confidence: 77%
“…McEnery & Nash (15) and Abinum et al (14) both independently found the coexistence of infantile cortical hyperostosis and WAS. This was a useful correlation to us in that the diagnosis in patient 6 became apparent because of radiological changes consistent with infantile cortical hyperostosis, and then led to specific investigations for WAS.…”
Section: Discussionmentioning
confidence: 98%
“…Three WAS patients have been reported with radiological and clinical features of infantile cortical hyperostosis (Caffey disease). 27 This rare and usually self-limited disease is characterized by increased width of bone cortex, resulting in bone expansion and bowing deformities. The frequency with which it appears in WAS is much higher than would be expected, but the etiological link has not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…In WAS, although development and absolute numbers of Tregs are normal, Tregs in WAS patients demonstrate an impaired ability to suppress the proliferation of activated T effectors cells and B cells in vitro [34][35][36]. Mouse experiments suggest an additional role for WASp in Treg peripheral homeostasis and normal tissue homing.…”
Section: Wasp Function and Activationmentioning
confidence: 99%
“…No associated genetic mutations were found, and following conservative management, a more typical WAS phenotype developed. Occasional WAS patients have been described with infantile cortical hyperostosis (Caffey disease), with inflammatory swelling of periosteum and overlying soft tissues [34]. With the coincidental finding of two rare conditions a shared pathophysiology of WAS and Caffey disease has been proposed.…”
Section: Atypical Presentationsmentioning
confidence: 99%